A Dual-Cycle Architecture in Cognitive M2M Wireless Networks. (19th November 2013) - Li, Ying; Dong, Xu; Wang, Lifeng; Guo, Xiaobo; Bai, Lin
Abstract : Dual-cycle cognitive model (DCCM) is an effective means to develop the future large-scale cognitive wireless networks. In this paper, the DCCM is considered to construct cognitive wireless netwroks, in which the structure and implementation of service-oriented radio architecture (SORA) are expounded. Using SORA, a DCCM-based wireless resource management is considered in design and implementation of cognitive wireless networks. It shows that our proposed DCCM-based SORA is able to provide loosely coupled, reusable, and scalable implementations in machine-to-machine (M2M) heteogeneous wireless networking environment, while the intelligence of network can be improved.